2004
DOI: 10.1128/jcm.42.2.764-768.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Multiresistant Streptococcus pneumoniae with Both erm (B)- and mef (A)-Mediated Macrolide Resistance

Abstract: Of a total of 1,043 macrolide-resistant Streptococcus pneumoniae isolates collected from 24 countries as part of PROTEKT 1999-2000, 71 isolates tested positive for both the mef(A) and erm(B) genes. Of 69 isolates subjected to further molecular investigations, all were resistant to tetracycline, 63 (91.3%) were resistant to penicillin, and 57 (82.6%) were resistant to trimethoprim-sulfamethoxazole. One isolate was also fluoroquinolone resistant, and another was resistant to quinupristin-dalfopristin. The ketoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
3
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 32 publications
5
61
3
3
Order By: Relevance
“…Isolates carrying both mef(A) and erm(B) have been reported previously (4,11,24) and are highly multidrug resistant (11), as the results of the present study have confirmed. This high-level resistance is most likely due to the presence of more than one mobile genetic element (11), but this hypothesis was not tested in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Isolates carrying both mef(A) and erm(B) have been reported previously (4,11,24) and are highly multidrug resistant (11), as the results of the present study have confirmed. This high-level resistance is most likely due to the presence of more than one mobile genetic element (11), but this hypothesis was not tested in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…In Japan, isolates with the mef(A) (40.3%) and the erm(B) (43.5%) genes are equally prevalent, but isolates with both erm(B) and mef(A) are relatively common (16.1%) (30). Interestingly, most erm(B) mef(A) isolates appear to belong to a multidrug-resistant clonal complex (11). Telithromycin is one of the few antibacterials to have good activity against this clone (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found one isolate that has both the mef(A)/ mef(E) and erm(B) genes and is closely related to Taiwan19F-14. Farrell et al have reported that such an isolate carries the mobile genetic elements Tn1545 and mega and suggested that the acquisition of such elements seems to be very effective in global dissemination (6). We therefore have to pay close attention to the increase of such isolates by continuous surveillance studies in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, описаны генетические ме-ханизмы формирования устойчивости стрептококков к макролидам. Первый вариант реализуется за счет приоб-ретения гена ermB (erythromycin-resistance methylase), что приводит к фенотипической устойчивости к эритромици-ну, кларитромицину, азитромицину и к клиндамицину [13]. Другой путь связан с приобретением генов mef, коди-рующих зависимые от ATФ белки, активно выводящие антибиотики из бактериальной клетки.…”
Section: контактная информацияunclassified